First-line immunochemotherapy for advanced NSCLC in Asian patients: a meta-analysis of phase 3 RCTs - Mao, Zhifang; Zhang, Zhiyong; Song, Meijiao; He, Jiaqi; Zheng, Jing; Liu, Wenquan (Frontiers in Oncology, 2025)
BackgroundPD-1/PD-L1 inhibitors plus chemotherapy (PC) are now broadly acknowledged as effective for treating stage IIIb–IV non-small cell lung cancer (NSCLC). However, data specific to Asian populations remain limited, and updated evidence from randomized controlled trials (RCTs) is warranted. In this study, the efficacy and safety of PC are analyzed and compared with those of chemotherapy in this population.MethodsSix databases were systematically explored to locate applicable phase 3 RCTs. Eligible studies involved Asian patients with stage IIIb–IV NSCLC and compared PC treatment with conventional chemotherapy. Overall survival (OS) and progression-free survival (PFS) were regarded as primary endpoints.ResultsA total of 16 phase 3 RCTs involving 4,452 Asian patients were included. Compared with chemotherapy alone, PC significantly improved OS (HR: 0.68 [0.63, 0.75], p < 0.00001, I2 = 30%) and PFS (HR: 0.50 [0.47, 0.54], p < 0.00001, I2 = 39%). The survival benefits were consistent across most subgroups and increased as survival time increased. The objective response rate (RR: 1.62 [1.51, 1.74], p < 0.00001, I2 = 0%) and disease control rate (RR: 1.09 [1.05, 1.12], p < 0.00001, I2 = 7%) were also better in the PC group. Brain metastasis and a PD-L1 CPS >50% were favorable factors in the PC group. However, more immune-related AEs (irAEs) were found in the PC group.ConclusionAmong Asian patients with stage IIIb–IV NSCLC, PC therapy still has a notable advantage in prolonging survival. Nonetheless, the increased frequency of AEs, particularly irAEs, warrants close attention.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251022604, PROSPERO identifier CRD420251022604.